VD_FINDINFO Décision / 2015 / 905 vom 3. Dezember 2015 - VD Tribunal cantonal (2015)
DOMMAGE IRRÉPARABLE, MESURE DISCIPLINAIRE, ASSISTANCE JUDICIAIRE | 38 LEP, 18 al. 1 LPA-VD, 18 al. 2 LPA-VD, 393 CPP (CH)